A HIGH-RESOLUTION LENSLESS FLUORESCENCE IMAGING SYSTEM USING MEMBRANE DEFLECTION FOR REDUCING GAP BETWEEN SAMPLES AND IMAGE SENSOR - Shin, Hyogeun; Choi, Woongsun; Yoon, Gun-Wook; Cho, Il-Joo; Choi, Nakwon; Yoon, Jun-Bo; Seo, Su Yeong (2018 IEEE MICRO ELECTRO MECHANICAL SYSTEMS (MEMS), 2018)
This paper reports on a high-resolution lensless fluorescence imaging system using membrane deflection for reducing the gap between fluorescent samples and a CMOS image sensor array. The presented system applied the principle of the total internal reflection of excitation light inside a PDMS chip to minimize the exposure of excitation light to the image sensor. We integrated a very thin (5.5 mu m) PDMS membrane as a flexible deflector, which allowed for significant reduction of the gap (-20 mu m) inevitably created during the conventional packaging (i.e., wire bonding) of image sensors. In the fabricated system, we achieved minimum distance of 7.5 mu m between fluorescent samples and an image sensor array. This reduced gap almost directly corresponds to a resolution as high as 7.5 mu m, based on the point spread function (PSF).